2019
DOI: 10.1002/mrm.27813
|View full text |Cite
|
Sign up to set email alerts
|

Highly accelerated multishot echo planar imaging through synergistic machine learning and joint reconstruction

Abstract: Purpose To introduce a combined machine learning (ML)‐ and physics‐based image reconstruction framework that enables navigator‐free, highly accelerated multishot echo planar imaging (msEPI) and demonstrate its application in high‐resolution structural and diffusion imaging. Methods Single‐shot EPI is an efficient encoding technique, but does not lend itself well to high‐resolution imaging because of severe distortion artifacts and blurring. Although msEPI can mitigate these artifacts, high‐quality msEPI has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 54 publications
0
64
0
Order By: Relevance
“…Nevertheless, with the utilization of additional constraints, it might be possible to devise new reconstruction scheme that can exploit the better phase estimates for specific applications. A similar idea is pursed in Ref . where the phase estimate from a SMS MUSSELS reconstruction was used in a second step of reconstruction using JVC‐SENSE to further improve the under‐sampled reconstruction by imposing additional constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, with the utilization of additional constraints, it might be possible to devise new reconstruction scheme that can exploit the better phase estimates for specific applications. A similar idea is pursed in Ref . where the phase estimate from a SMS MUSSELS reconstruction was used in a second step of reconstruction using JVC‐SENSE to further improve the under‐sampled reconstruction by imposing additional constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The smoothness regularization incorporated in the SR SMS MUSSELS helps the recovery of the partial Fourier data by providing an additional constraint. Several studies have also showed the utility of a conjugate symmetry‐based regularization which can be extended to the SMS MUSSELS framework . Implementations similar to Ref .…”
Section: Discussionmentioning
confidence: 99%
“…Using piecewise smooth signal model, we have shown the recovery of 8‐shot data using SR‐MUSSELS in from a 32‐channel acquisition, which is also partial Fourier accelerated. The recovery of 9‐shot data from a 32‐channel acquisition using MUSSELS was recently shown in …”
Section: Discussionmentioning
confidence: 99%
“…In Figure of Supporting Information, we show the results of a shot‐accelerated reconstruction using IRLS MUSSELS with CS using three out of the four shots. The capability of MUSSELS to reconstruct highly (shot‐) accelerated msEPI was reported in also. Further, the extension of MUSSELS to incorporate slice acceleration was also demonstrated using real SMS‐accelerated scans in and simulations in .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation